Propuesta de reforma legal al capítulo v, del procedimiento legislativo, sección 1, trámite de aprobación de leyes ordinarias y de urgencia en materia económica, artículos 61 y 62 de la ley orgánica de la función legislativa - Mafla Herrería, Edgar Fernando (2014)
The National Assembly since its creation as such, a legal technician legislative action during this time period analysis /, seems to me to comment on some relevant data Citizen Participation Corporation has been obtained through its oversight of the National Assembly. It seems important to note that in relation to the legislative initiative, we observe some important data. It should be noted that when we refer to initiatives, has to do with all proposals admitted, but with those who have been admitted for consideration by the Legislative Council of Administration (CAL). Of this group, it appears that a significant number of government belong to the block, and the Executive; believe that the latter may be due to the fact that the First Transitory Provision of the Constitution establishes the obligation of mandatory way to pass important laws for a specified period, as is well known, is limited to the amount and importance of laws provided . Thus, we see that the majority of projects that process is started (some have ended and some not), come from the legislature, most of the official bloc (the opposition has filed several projects, but among those admitted, the block official predominate). As for the initiative out of the Assembly, the Executive projects predominate, with little legislative initiative (at least in projects supported), both autonomous bodies, the citizenship. Regarding the mechanisms for debate and passage of legislation, the Assembly of Montecristi, approved the content of the laws is discussed and approved in a bundle and not for items like the previous legislation. This has been the issue that has generated more concern. Certainly, we must recognize that some laws have undergone major public processes and mechanisms of socialization, especially in its treatment Commissions. However, we believe that already in the voting process, do-in the second and final debate-for complete projects, or "iron" does not contribute positively to the process of building laws. In this regard, the report of oversight of the Corporation Citizen Participation, the Legislative Audit Commission, when it culminated in office the transitional legislative body, one of the recommendations made was to review the ongoing process in the former Organic Law of the Legislative Branch and its regulations, where it is anticipated that at least the items of a project that have been observed which are generally the polémicos-, to discuss and vote individually. This allows citizens and general public to identify the positions of each legislator in each individual issue beyond the position you have about the project as a whole, facilitating accountability and to transparency. On the other hand to identify and correct more easily, drafting flaws, errors in reference to other laws or articles of the same law, repetitions of standards, etc. In the same vein, we believe that establishing deadlines for issuing reports, does not contribute to quality. The adoption of legislation should have all the time needed for the analysis is appropriate, thorough and neat. An appropriate institutional design and successful operation of law agencies must reconcile the principle of the speed with the need for efficiency and proper debate. So dangerous it is for institutions, poor legislative production as a generous spread of laws in the rush to meet a deadline, or the absence of an individualized discussion of controversial issues, these are issued without rigor, detail and time sufficient legal technique recommended.